The Analysis of Heat Pump Performance Using R-410A for Drying - ทุริสุทธิ์, ณัทกร; ลิมปิทีปราการ, เทิดเกียรติ; ทองวิค, สถาพร; นิมมล, ฉัตรชัย (Frontiers in Engineering Innovation Research, 2012)
This research was conducted to study a performance of heat pump dryer system with selected products of a paddy. The comparison between the experimental drying and the mathematical modeling of heat pump dryer was found to have an error value. Data analysis and the system defect were made. The studies aims to selected the refrigerant that can be use in safety and friendly for global warming protection. The compared valuables were the coefficient of performance of heat pump (COP[subscript h]), and drying rate (DR). This study has two part, the first part was made by comparing between the 8 m3 heat pump dryer and the mathematical modeling with R-22. The study was found to have error of (COP[subscript h]) as 3.6 %. Therefore can be used this modeling simulate to the (COP[subscript h]) in the second part, this modeling used to compare between R-4I0A and R-22 with equivalent heat pump capacity. It was found that the (COP[subscript h]) of R-410A was higher than R-22 about 62 % but the average DR of R-410A lower than R-22 about 5.5 %. Therefore, the R-410A is suitable to replace the R-22 for a heat pump dryer in the future.